Educational assistance and education quality in Indonesia: The role of decentralization - Virgi Sari (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
We examine the evolution of educational assistance in Indonesia, following two decades of government decentralization, and its effect on education quality. Using Indonesia Family Life Survey data, we exploit as exogenous rule the variation in the implementation of government decentralization to compute difference-in-difference estimators. Indicative evidence suggests decentralization has facilitated collusion between village authorities and marginalized private schools, with substantial increases in educational assistance and financial resources, especially to religious schools. Despite dominant rent-seeking behaviour and self-interest motives, increased public resource allocation to private schools impacted positively on student achievement. Our results also emphasize the role of social norms in undermining efficient public goods allocation after decentralization.
Keywords: H52; H53; I28; I38; 330; decentralization; education transfer; education quality; difference-in-difference; semi-parametric estimation; Indonesia